Management of the potential paediatric organ donor. Issue 5 (May 2019) - Reynolds, David; Vyas, Harish; Silvestre, Catarina
Abstract: Paediatric organ donors remain a critically scarce and precious resource at a time of ever increasing demand for donor organs. The early recognition and management of the potential paediatric organ donor can increase the number of viable donor organs available. Managing the cardiovascular instability that follows brain death requires a systematic intensive care approach in order to preserve viability of the potential donor organs. Careful consideration of the fluid status and inotrope requirements in addition to supplementation of the hormonal and haematological axes helps to optimize tissue perfusion. This paper seeks to summarize the physiology that occurs following death and review current management strategies within the paediatric intensive care setting.